Extracellular recombinant production of 4,6 and 4,3?-glucanotransferases in Lactococcus lactis - Biyikli, Ayse; Nicin, Ramazan Tolga; Dertli, Enes; Simsek, Omer (ELSEVIER SCIENCE INC, 2023)
4,6 alpha-Glucanotransferase (4,6-alpha-GTase) and 4,3 alpha-glucanotransferases (4,3-alpha-GTase) produced by Lactic Acid Bacteria (LAB) in the GH70 enzyme family have become important due to their catalytic effect on starch and maltodextrins. Their high level of production is necessary for their application at industrial scale. In this respect, both enzymes were expressed extracellularly using Lactococcus lactis as GRAS host. 4,6-alpha-GTase and 4,3-alpha-GTase genes from Limosilactobacillus reuteri E81 and Limosilactobacillus fermentum PFC282 respectively were trans-formed into the plasmid pLEB124 vector having the signal peptide usp45 under the P45 continuous promoter and successfully expressed in Lactococcus lactis MG1363. Western blot screening showed that the relevant enzymes were able to be successfully secreted extracellularly. The Vmax and Km of 4,6-alpha-GTase were 2.58 mu mol min-1 and 0054 mg min-1 whereas 3369 mu mol min-1 and 0032 mg min-1 for 4,3-alpha-GTase respectively. NMR analysis demonstrated the formation of new bonds within the corresponding enzymes. Also, both enzymes were active on maltose, maltoheptaose, maltohexaose and starch and produced malto-oligosaccarides observed by TLC analysis. In conclusion, this study demonstrated first time the extracellular production of 4,6-alpha-GTase and 4,3-alpha-GTase with GRAS status that can be useful for starch retrogradation delay and glycaemic index reduction.
Keywords: Glucanotransferase; Extracellular production; Lactococcus lactis; Starch; 4,6-ALPHA-GLUCANOTRANSFERASE; Biotechnology & Applied Microbiology